Exposure-response Relationship and Chemical Characteristics of Atmospheric Odor Pollution from a Cigarette Factory - Weihua Yang; Weifang Li; Yan Zhang; Meng Han; Zengxiu Zhai; Huanwen Cui (Aerosol and Air Quality Research, 2022)
Abstract Odor pollution is one of the most complained environmental problems in China. At present, the odor control is mainly aimed at municipal facilities. There is a lack of reports on the atmospheric odor pollution produced by some special industrial emissions. This paper studied the odor impact of a cigarette factory on surrounding residents in order to obtain the exposure-response relationship, which can provide a scientific basis for odor control of cigarette production. Exhaust emission measurement, sample collection and laboratory analysis, as well as community survey were carried out. The air dispersion model Aermod was used to simulate the olfactory odor concentrations in surrounding residential areas. Face-to-face questionnaire was used to collect the information of residential responses to the cigarette odor. The exposure-response relationship between the percentage of highly annoyed people (%) and the 98th percentile of odor concentrations was analyzed using the univariate binomial logistic model. In addition, the typical odor pollutants were found by odor activity value. The results showed that the proportion of highly annoyed people in the residential area was ranged from 5% to 64%, and the acceptable level of exposure odor concentration was 4 OU m−3 at the 98th percentile. The main odor substances of the cigarette factory were oxygenated organic substances including esters, fatty acids and ketones. Based on the chemical composition and the odor character of each substance, the odor wheel of cigarette factory was established for the first time.